Index Finger Pointing (Likely a Subtle Form of Hand Dystonia): Prevalence Across Movement Disorders - Vives-Rodriguez, Ana; Louis, Elan D. (Frontiers in Neurology, 2018)
Objective: To investigate the prevalence of index finger pointing (IFP) while walking, which is likely a subtle form of hand dystonia, in cranio-cervical focal dystonia syndromes, Parkinson’s disease (PD), essential tremor (ET), and controls. Methods: We recruited patients with an established diagnosis of PD, dystonia, or ET and healthy controls. All participants were videotaped while walking. Videotapes were evaluated by the authors, blinded to diagnosis, to assess the presence or absence of IFP. Results: Two-hundred-fifty participants included 50 dystonia, 50 PD, 80 ET and 70 controls. IFP was present in 29/250 (11.6%) participants: 10 dystonia (20.0%), 8 PD (16.0%), 8 ET (10.0%) and 3 controls (3.8%) (p = 0.03). There was a significant evidence of a trend in the odds of having this sign among disorders with higher risk of dystonic features (dystonia>PD>ET>control; test for trend = 0.004). Among the 180 patients (dystonia, PD, and ET, i.e., excluding the 70 controls), IFP was present in 26 (14.4% prevalence). Conclusion: IFP during gait, likely a subtle form of hand dystonia, was observed in 14.4% of movement disorder patients. The highest prevalence was in dystonia, the second highest in a disease that is often accompanied by dystonia (PD), a lower prevalence among individuals with a disease that is rarely accompanied by dystonia (ET), and the lowest in controls.